Analisis Penggunaan Konten Sosial Media Pada Umkm Terhadap Minat Beli Konsumen Di Kota Gunugsitoli - Gulo, Yenni Tri Yanti; Ndraha, Anjes Tatema Jefanya; Haria, Reklis Putri; Zendrato, Sejoiman (CV. SINAR HOWUHOWU, 2025)
Social media has emerged as one of the most effective marketing tools for developing businesses, especially in the micro, small and medium enterprise (UMKM) sector. The aim of this research is to analyze the impact of social media content owned by UMKM on consumer purchasing intentions in Gunungsitoli. This study uses a qualitative approach and interview methods to research UMKM owners and consumers in Gunungsitoli. The findings of this study indicate that social media content quality, engagement, and posting consistency are critical to driving consumer buying habits. This study provides UMKM in Gunungsitoli with a better understanding of consumer behavior in the digital era.